Stealth export of hydrogen and methane from a low temperature serpentinization system - Larson, B I; Lang, S Q; Lilley, M D; Olson, E J; Lupton, J E; Nakamura, K; Buck, N J (Deep-Sea Research Part II: Topical Studies in Oceanography, 2015)
Chemical input to the deep sea from hydrothermal systems is a globally distributed phenomenon. Hydrothermal discharge is one of the primary mechanisms by which the Earth's interior processes manifest themselves at the Earth's surface, and it provides a source of energy for autotrophic processes by microbes that are too deep to capitalize on sunlight. Much is known about the water-column signature of this discharge from high-temperature mid-ocean Ridge (MOR) environments and their neighboring low-temperature counterparts. Hydrothermal discharge farther away from the ridge, however, has garnered less attention, owing in part to the difficulty in finding this style of venting, which eludes methods of detection that work well for high-temperature ‘black smoker'-type venting. Here we present a case study of the plume from one such ‘invisible' off-axis environment, The Lost City, with an emphasis on the dissolved volatile content of the hydrothermal plume. Serpentinization and abiotic organic synthesis generate significant concentrations of H2 and CH4 in vent fluid, but these species are unevenly transported to the overlying plume, which itself appears to be a composite of two different sources. A concentrated vent cluster on the talus slope channels fluid through at least eight chimneys, producing a water-column plume with the highest observed concentrations of CH4 in the field. In contrast, a saddle in the topography leading up to a carbonate cap hosts broadly distributed, nearly invisible venting apparent only in its water-column signals of redox potential and dissolved gas content, including the highest observed plume H2. After normalizing H2 and CH4 to the 3He background-corrected anomaly (3He$Δ$) to account for mixing and relative amount of mantle input, it appears that, while a minimum of 60{%} of CH4 is transported out of the system, greater than 90{%} of the H2 is consumed in the subsurface prior to venting. The exception to this pattern occurs in the plume originating from the area dubbed Chaff Beach, in which somewhat more than 10{%} of the original H2 remains, indicating that this otherwise unremarkable plume, and others like it, may represent a significant source of H2 to the deep sea.
Keywords: AUV ABE (Autonomous Benthic Explorer); HOV Alvin (Human Occupied Vehicle)